Diversificação e radiação recente de Stryphnodendron adstringens (Leguminosae) no cerrado: consequências genéticas frente às mudanças climáticas - Braga, Ramilla dos Santos (2019)
The species Stryphnodendron adstringens (barbatimão) is considered a valuable genetic resource of the Brazilian Cerrado, mainly due to its medicinal properties. It has been exploited in an extractive manner in its natural habitat, requiring studies of conservation and management plans. Species of this genus had recent diversification in the Cerrado, becoming interesting models for evaluating intraspecific genetic patterns in the biome. In this context, the objective of this work was to evaluate the phylogeographic patterns of S. adstringens, in order to infer about the hypotheses of diversification of their lineages in time and space. Beyond to measure the impact of future climate changes on the geographic distribution of the genetic variation of this species. For this, the DNA polymorphism of chloroplastid (psbA-trnH and trnL-F) and nuclear (ETS) regions was quantified in individuals from 17 localities in the Cerrado. Haplotype and nucleotide diversity levels were evaluated to verify the population genetic differentiation. Coalescence analyses were performed to estimate historical demographic parameters and to identify divergence time among populations of S. adstringens. The environmental suitability of S. adstringens in the past, present and historical refuge was used to identify spatial patterns on population genetic diversity. Current and future genetic clusters were simulated from climatic scenarios. Low genetic diversity was found for cpDNA and ETS and the geographical distribution of haplotypes reflects an incomplete lineage sort. There are discordant patterns of interpopulation genetic differentiation between regions of the genome, with greater effect for cpDNA. Historical demographic equilibrium was evidenced for S. adstringens, contrary by ENM, indicating retraction of range. Most recent common ancestor was dated to 1.7 Ma ago, dividing into two main clades with most of the diversification events dating to the Middle Pleistocene. The spatial structure is stronger for ETS, suggesting the existence of isolation by distance and environmental isolation due to temperature variations. Populations closer to the edge of the historic refuge have greater genetic diversity that can be associated with multiple historical refuges and ecological transition from forest to savanna environments. Genetic clusters modeled under current and future climatic conditions, indicate losses and homogenization of genetic variation for the species. The data corroborate the recent population diversification of S. adstringens in the Cerrado, reinforcing the phylogenetic pattern in species of this genus. Beyond, low levels of genetic diversity, reflecting the effects of glacial and interglacial periods in the Pleistocene, suggesting multiple refuges formation. The impact of climate change and the disorderly exploitation of the natural populations of this genetic resource indicate the need for management and conservation plans of the species.